Políticas de fomento à pesquisa: implementação e efeitos do PIPEq na PUC-SP - Ferraz, Luanda (2022)
This research aims to study research promotion policies and specifically analyzes the Research Incentive Plan (PIPEq) of the Pontifical Catholic University of São Paulo (PUCSP). The central question is related to the effects that its implementation has exerted on the professors and academic bodies (courses, and faculties) of the University, both with regard to the production/dissemination of research in the totality of each modality and in the temporal succession from 2015 to 2020. The general objective is to analyze its inter-area and intra-institutional effects (courses, colleges and professors), considering the relationship between the availability of funding and the production/dissemination of research. As specific objectives, it was defined to measure the flows of financing demand, considering the various modalities; analyze them both in the relationship between themselves and temporally; and to analyze the differential impacts that the available resources generated between professors and interarea and intra-institutional areas, in terms of incidence between colleges and undergraduate and graduate courses stricto sensu. To this end, data on the modalities offered in the first six years of its implementation (2015 - 2020) were organized for the analysis of trends, through statistical data generated by the Software Sphinx iQ2. The data were analyzed in the light of the concept of scientific field (BOURDIEU, 1983, 2004a, 2004b; BOURDIEU; WACQUANT 2005, 2007) to understand the distinctions that the resources available for research promotion have generated between courses; the faculties, the areas of knowledge and the level of insertion of teachers. The results obtained reveal significant increase in the number of productions of professors, pointing out that PUC-SP has an area of consolidated vocation, resulting from its identity, since the university assumes its critical position in the debate for the social and academic relevance of the quality of its intellectual productions, added to the history and trajectory of construction and consolidation of the scientific field, which leads us to consider that PIPEq was fundamental for the continuity and maintenance of the research carried out. The comparison through bibliometric indicators, after the implementation of PIPEq, pointed out that the results were successful because there is a recurrence in the increase of publications and citations in national and international platforms from 2015. The effects and efforts of PIPEq seem to be significant for support for professors in the consolidation of research in human and social sciences, expressed especially with the increase in scientific production at PUC-SP